Sintesis dan Karakterisasi Hidroksiapatit Cangkang Rajungan dengan Variasi Suhu Kalsinasi dan Konsentasi KH2PO4 menggunakan Metode Presipitasi Sebagai Sediaan Biomaterial Implan Tulang - Romadhona, Novelia Gita; Syafira, Nesha Permata; Gumelar, Tobing; Rizqiyah, Vita Fatichah; Ningrum, Eva Oktavia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Bone implants are mostly made of non-degradable metal materials that are toxic to the body. An alternative biodegradable material being developed is Poly-L-Lactic Acid (PLLA). However, PLLA has the disadvantage of being incompatible with bone tissue. So, materials that are biodegradable and biocompatible are needed, such as hydroxyapatite, which has similarities with the minerals in bone and teeth, it suitable as an alternative biomaterial in the biomedical. This research aims to determine the effect of synthesis conditions, with calcination temperature (850, 900, 950, 1000°C) and KH2PO4 concentration (0.25, 0.5, 0.75, 1 M), on the production of hydroxyapatite using raw materials from local blue crab shells, in terms of calcium content, functional group presence, and conformity of hydroxyapatite peaks with JCPDS 09-0432. The synthesized product was characterized using XRF, which showed a relatively high calcium in crab shells of 94.89% at calcination temperature 850°C. The FTIR test results after the mixing of KH2PO4 with CaO showed the formation of hydroxyapatite functional groups, namely OH- and PO43-, in all variables. The XRD test results showed that at 850°C and KH2PO4 concentration of 0.75 M the main peak of hydroxyapatite was closest to JCPDS 09-0432, at a diffraction angle (2θ) of 31.7634.